Can a language be before “the first programming language”? - Menyhárt, László (Teaching Mathematics and Computer Science, 2011)
I would like to present a potential new language which can be before "the first programming language". We can use this to write down the algorithms and source code can be generated from this. The keyword is XML. This can be used for describing algorithms, easy to check the syntax and the semantic. Source code can be transformed with XSLT. So the usage of this new language can help us to answer the question, which is the best first programming language?